Cochlear Implantation in a Child With Hypoplastic Left-heart Syndrome: Clinical Case - Margarita S. Kalugina; Yuri Yu. Rusetskiy; Andrei E. Aleksandrov; Aleksandr V. Pashkov; Ul'yana S. Malyavina; Elena A. Alekseeva (Педиатрическая фармакология, 2019)
Relevance. The hypoplastic left-heart syndrome at congenital heart disease has frequency of 261 cases out of 10,000 newborns. Children with hypoplastic left-heart syndrome can have comorbid congenital anomalies and acquired diseases that require treatment and are associated with high mortality risk.Description of a clinical case. Female patient, 6 years 4 months, with the hypoplastic left-heart syndrome was admitted to our hospital with the diagnosis «Sensorineural hearing loss, speech delay» for performing of cochlear implantation. The council of physicians was convoked before the surgery to coordinate patient management. Members of surgical, anesthesiology, laboratory and instrumental examination departments were involved into preoperative assessment and planning due to the high level of surgical and anesthetic risk. The patient was dismissed from hospital on the 10th day after cochlear implantation. The patient has undergone the course of auditory-verbal therapy a month after. The child was dismissed wit state improvement.Conclusion. The example of successfully performed surgery in the patient with hypoplastic left-heart syndrome and such severe comorbid pathology as sensorineural hearing loss is presented. Complete physical examination of the child in preoperative period and adequate preparation for the surgery were the key factors for patient successful management and further rehabilitation.